2020
DOI: 10.3390/ijms21124320
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes in the Normal and Pathological Peripheral Nervous System

Abstract: We studied telocytes/CD34+ stromal cells in the normal and pathological peripheral nervous system (PNS), for which we reviewed the literature and contributed our observations under light and electron microscopy in this field. We consider the following aspects: (A) general characteristics of telocytes and the terminology used for these cells (e.g., endoneurial stromal cells) in PNS; (B) the presence, characteristics and arrangement of telocytes in the normal PNS, including (i) nerve epi-perineurium and endoneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 103 publications
5
45
0
Order By: Relevance
“…In a previous review on TCs/CD34+SCs in the peripheral nervous system, we highlighted the behaviour of these cells in neuropathies of the appendix and gallbladder [ 43 ]. Using confocal microscopy, we then studied the involvement of adipose tissue in appendicular hyperplastic neurogenic processes.…”
Section: Tcs/cd34+scs In Pathologically Affected Adipose Tissuementioning
confidence: 99%
“…In a previous review on TCs/CD34+SCs in the peripheral nervous system, we highlighted the behaviour of these cells in neuropathies of the appendix and gallbladder [ 43 ]. Using confocal microscopy, we then studied the involvement of adipose tissue in appendicular hyperplastic neurogenic processes.…”
Section: Tcs/cd34+scs In Pathologically Affected Adipose Tissuementioning
confidence: 99%
“…Fibroblasts are another important cell type in peripheral nerves; they are the most abundant cells in the endoneurium, perineurium and epineurium and provide structural support, regional separation and protection of nerve fibers from damage (Parrinello et al, 2010 ; Stierli et al, 2018 ; Carr et al, 2019 ; Diaz-Flores et al, 2020 ). They have mesenchymal cell properties and play an important role in nerve repair following injury (Parrinello et al, 2010 ; Carr et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…They have mesenchymal cell properties and play an important role in nerve repair following injury (Parrinello et al, 2010 ; Carr et al, 2019 ). We tested marker genes for fibroblasts reported in previous mouse sciatic nerve scRNA-seq studies including: Sfrp4, Pi16, Dpt, Gsn, Col1a1, Col1a2, Col3a1, Col14a1, Clec3b, Cygb, Prrx1, and Aebp1 (Carr et al, 2019 ; Diaz-Flores et al, 2020 ; Toma et al, 2020 ; Wolbert et al, 2020 ). We found that some of these genes are not fibroblast-specific and that while some of them were fibroblast specific, they only label one sub-population of epineurial, perineurial or endoneurial fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the extensive distribution of TC interstitial networks in different organs and the numerous putative roles attributed to these stromal cells, increasing literature has hypothesized that their phenotypic and functional alterations may be implicated in different pathologic conditions [ 28 , 29 , 30 , 31 ]. Indeed, recent studies have reported a reduction in TCs and severe structural changes in the TC stromal network in a variety of disorders, including heart failure and conditions characterized by chronic tissue inflammation and/or fibrotic remodeling, such as psoriasis, primary Sjögren’s syndrome, Crohn’s disease, ulcerative colitis, systemic sclerosis, and liver fibrosis [ 24 , 28 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%